The Evolution of Photoluminescence Properties of PEA2SnI4 Upon Oxygen Exposure: Insight into Concentration Effects. (7th October 2021) - Ju, Yangyang; Wu, Xian‐gang; Huang, Sheng; Dai, Guang; Song, Tinglu; Zhong, Haizheng
Abstract: The time evolution of the photoluminescence properties in phenylethylammonium tin halide perovskite (PEA2 SnI4 ) film as a function of oxygen concentration is reported. Photo‐brightening and reversible photoluminescence quenching are observed in PEA2 SnI4 film at ultralow oxygen concentration (< 1.5 vol%). In the case of 1.5 vol% < [O2 ] < 21 vol%, the photoluminescence emission of PEA2 SnI4 film can be partially recovered after resetting the samples to nitrogen box. As the oxygen concentration further increases with the range of 21 to 95 vol%, the photoluminescence emission of PEA2 SnI4 film is significantly quenched and can only be slightly recovered after removing it to the nitrogen box. By correlating the material characterizations and theoretical analysis, the interactions between PEA2 SnI4 and oxygen contain physisorption and chemical reactions are illustrated. Depending on the oxygen concentration, the chemical reactions between PEA2 SnI4 and oxygen can be reversible and/or irreversible. The insights into oxygen concentration effects provide a guideline to optimize the stability of PEA2 SnI4 for achieving high‐performance optoelectronic devices. Abstract : The temporal evolution of photoluminescence properties in phenylethylammonium tin halide perovskite (PEA2 SnI4 ) film as a function of oxygen concentration is reported. The insights into the oxygen concentration effects provide a guideline to optimize the stability of PEA2 SnI4 for achieving high‐performance optoelectronic devices.